2017
DOI: 10.1017/ice.2017.239
|View full text |Cite
|
Sign up to set email alerts
|

Relative Resistance of the Emerging Fungal Pathogen Candida auris and Other Candida Species to Killing by Ultraviolet Light

Abstract: Mobile ultraviolet-C (UV-C) light room decontamination devices are frequently used as an adjunct to standard cleaning in healthcare facilities, but their efficacy in killing Candida species is not clear. In laboratory testing, the emerging multidrug-resistant Candida auris and 2 other Candida species were significantly less susceptible to killing by UV-C than methicillin-resistant Staphylococcus aureus. Infect Control Hosp Epidemiol 2018;39:94-96.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 9 publications
1
67
4
2
Order By: Relevance
“…154 CDC further states that when the use of products on List K is not feasible, published research has found that the following products led to a substantial reduction 154 Room disinfection with a UV-C device has been investigated for its ability to inactivate Candida spp, MRSA, and Clos difficile. 155 C auris demonstrated substantially less susceptibility to UV-C than MRSA and less susceptibility than C albicans or C glabrata at 10 minutes exposure time. 155 Reductions in C auris and Clos difficile were similar at 10 minutes.…”
Section: Susceptibility To Germicidesmentioning
confidence: 88%
See 2 more Smart Citations
“…154 CDC further states that when the use of products on List K is not feasible, published research has found that the following products led to a substantial reduction 154 Room disinfection with a UV-C device has been investigated for its ability to inactivate Candida spp, MRSA, and Clos difficile. 155 C auris demonstrated substantially less susceptibility to UV-C than MRSA and less susceptibility than C albicans or C glabrata at 10 minutes exposure time. 155 Reductions in C auris and Clos difficile were similar at 10 minutes.…”
Section: Susceptibility To Germicidesmentioning
confidence: 88%
“…155 C auris demonstrated substantially less susceptibility to UV-C than MRSA and less susceptibility than C albicans or C glabrata at 10 minutes exposure time. 155 Reductions in C auris and Clos difficile were similar at 10 minutes. 155 With regard to room disinfection devices, the CDC states that "data on hands-free disinfection methods, like germicidal UV irradiation, are limited, and these methods may require cycle times similar to those used to inactivate bacterial spores (eg, Clostridium difficile) when used for C auris."…”
Section: Susceptibility To Germicidesmentioning
confidence: 88%
See 1 more Smart Citation
“…86 Non-touch disinfection techniques UV-C light (254 nm with 10 min exposure time) is less effective for C. auris than methicillin-resistant Staphylococcus aureus although increasing exposure times to 20-30 min significantly increased the efficacy. 90 Dry gasvaporised H 2 O 2 (8 g peroxide/m 3 ) resulted in killing of 96.6-100% C. auris isolates in another report, although strain resistance varied significantly. 88…”
Section: Cleaning and Disinfection Agentsmentioning
confidence: 93%
“…UV‐C light (254 nm with 10 min exposure time) is less effective for C . auris than methicillin‐resistant Staphylococcus aureus although increasing exposure times to 20–30 min significantly increased the efficacy . Dry gas‐vaporised H 2 O 2 (8 g peroxide/m) resulted in killing of 96.6–100% C .…”
Section: Infection Prevention and Control Measuresmentioning
confidence: 99%